Program Evaluation in Language Education - Kiely, R. author. aut Link
XII, 311 p.
Keywords: The authors describe evaluation as a way of understanding and developing language programs: the thematic and background section sets out the decision-making, quality management, and learning functions of evaluation. Case studies illustrate the diversity of evaluation contexts, functions and approaches, documenting the ways in which evaluation processes and outcomes inform and facilitate program development, and contribute to explaining how language and teacher education programs constitute opportunities for learning. The ways in which evaluation practice can be researched and developed to maximize policy, institutional and program effectiveness is included, and a comprehensive set of resources for those commissioning, undertaking or researching language program evaluations concludes the text.